The Effect of Career Development and Training on Organizational Performance : the Mediation Role of Employee Competence - M Ryan Alvarezy; Ani Jamiyati; Trisno Ajisantoso Bagusromadhan; Pupung Purnamasari (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the influence of Career Development and Training on Organizational Performance with Employee Competence as a mediating variable. In the context of a dynamic business environment, the role of employee competence is crucial in transforming Human Resources (HR) initiatives into tangible company performance. Data was obtained through in-depth interviews with a number of employees from various levels of positions. The results show that Employee Competence has a positive and significant effect on Organizational Performance. Furthermore, Training was found to have an influence on Organizational Performance only indirectly, proving Full Mediation by Employee Competence. Meanwhile, Career Development showed a dual influence, namely direct and indirect, indicating Partial Mediation. These findings underscore the importance of HR strategies that focus on competency improvement outcomes as a primary prerequisite for investments in training and career development to contribute optimally to organizational performance.